Study of risk factors, clinical profile, and outcome in meconium-stained deliveries - Shukla, Omprakash S; Swapna, S T (Indian Journal of Child Health, 2019)
Background: The presence of meconium in amniotic fluid is a serious sign of fetal distress which leads to an increase in neonatal mortality. Objective: The objective of this study was to study the risk factors, clinical profile, and outcome of babies born through meconium-stained fluid. Materials and Methods: This prospective observational study was conducted during the period from February 2018 to October 2018 at neonatal unit of a tertiary care hospital. All live babies delivered through meconium-stained liquor were included in this study. Routine investigations such as complete blood count and C-reactive protein were done in all the patients. All the variables were analyzed with the help of the Chi-square test and Fisher’s exact test. Results: A total of 606 meconium-stained amniotic fluid (MSAF) babies were included in the study. Most of the MSAF babies were term, appropriate for gestational age babies. The number of babies delivered through the lower segment cesarean section was 61.7%. Fetal distress was present in 23.2% of the cases. Otherwise, the most common risk factor associated with MSAF was pre-eclampsia (5.9%). A total of 58.2% of babies developed respiratory distress after birth; other morbidities associated were convulsion, hypoxic-ischemic encephalopathy, sepsis, shock, hypoglycemia, and hyperbilirubinemia. In the present study, total mortality in MSAF babies was 12%. Babies who expired had severe meconium aspiration syndrome. Duration of hospital stay was